Exploration and practice of PRIDE teaching mode oriented to cybersecurity talent cultivation - Jianwei LIU; Dawei LI; Ying GAO; Yu SUN; Hua GUO (网络与信息安全学报)
In the long-term practice of cybersecurity talent cultivation, the teaching team of School of Cyber Science and Technology of Beihang University, aiming at the knowledge goal, ability goal and quality goal of talent cultivation of cybersecurity discipline and related majors, puts forward the innovative teaching idea of “fine teaching, strong practice, excellent assessment, abundant resources” according to the knowledge characteristics, thinking characteristics and psychological characteristics of students.The teaching team integrates political teaching,research teaching, inspiration teaching, seminar teaching and example teaching methods, puts forward the PRIDE teaching mode，which has been widely applied in the teaching of core professional courses such as “Information Network Security” and “Modern Cryptography”, and has got remarkable teaching achievement.Through the practice of PRIDE teaching mode, a high-level teaching team with high political quality and strong teaching ability has been also built.